(untitled) (Письма в ЭЧАЯ, 2024)
Mass spectra of quarkonium systems can be described by different phenomenological potentials. In the present work, we explored theoretical analysis methods for energy spectra of diatomic molecules and heavy mesons, the resonance states (cc and bb) of heavy quarkonium were considered the rovibrational states. A parameterized rovibrational model was derived from the empirical solution of the nonrelativistic Schr"odinger equation with Morse potential. The corrections were composed of color hyperfine interaction and spin-orbit interaction of mesons. The high excited state mass spectra of charmonium and bottomonium were obtained after comparing the results with the present experimental data in a fair manner. Our calculations show that the modified rovibrational model can be used in the meson system of quark and anti-quark, thereby proving to be useful for the interpretation of excited hadron spectra.